Estimating glycemic index of rice-based mixed meals by using predicted and adjusted formulae - Osman, Nur Maziah Hanum; Mohd Yusof, Barakatun Nisak; Ismail, Amin (China National Rice Research Institute, 2017)
The estimation of glycemic index (GI) of rice-based mixed meal either by using predicted GI (GIpred) or adjusted GI (GIadj) formula is unclear. This study aimed to determine the glycemic response of rice in rice alone or mixed meals and to identify the appropriate formula for estimating the GI of rice-based mixed meals. The glycemic responses produced by the rice alone (red rice, fragrant white rice or parboiled rice) and the rice-based mixed meals (fried red rice, fried fragrant white rice or fried parboiled rice) which provided 25 g available carbohydrate were assessed in 11 healthy individuals. To determine the measured GI (GImeasured) of rice alone and rice-based mixed meals, participants underwent three repeated tests of a reference food (Glucolin®). Tests were performed in random order on nine separate visits after an overnight fasting for at least 8 h. Capillary glucose at baseline (0 min), 15, 30, 45, 60, 90 and 120 min from starting the meals was assessed and used to determine the incremental area under the curve (iAUC120). The agreement between GImeasured and the estimation formulae (GIpred or GIadj) were determined using Bland-Altman analysis. The iAUC120 after consuming rice alone was significantly higher than the rice-based mixed meals except for fried fragrant rice, which was comparable to the rice alone (P > 0.05). The GImeasured values of rice were categorized as medium (61 for parboiled rice, 67 for fragrant white rice, and 68 for red rice). GIpred (r = 0.40, P < 0.01) and GIadj (r = 0.41, P < 0.01) were significantly correlated with iAUC120. The agreement between GImeasured and GIadj is apparent suggesting the usefulness of GIadj in estimating meal GI of rice-based mixed meals.